APPLICATIONS OF BRANCH-BOUND ALGORITHM TO SOLVE SOME OPTIMAL PROBLEMS RELATED TO THE HAMILTONIAN CYCLE BASED ON THE TSP - Đỗ Như An (Tạp chí Khoa học Đại học Đà Lạt)
The Traveling Salesman Problem (TSP) is the most prominent of the combinatorial optimization problems that belongs to NP-Hard. The best algorithm for solving TSP is the branch-bound algorithm with exponential-time complexity. This paper presents how to use the branch-bound algorithm to solve some of the combinatorial optimization problems related to the Hamiltonian cycle based on the TSP.